PENGARUH KONSENTRASI PEREKAT TERHADAP LAMA BAKAR DARI RDF AMPAS KOPI DAN AMPAS TEBU - Fery Surya Ramadhan; Danar Susilo Wijayanto; Husin Bugis (Nozel : Jurnal Pendididikan Teknik Mesin, 2019)
New and renewable energy (EBT) is a source of energy that can be created by humans by utilizing solid waste from industrial processing. One example of making renewable energy is RDF. Refuse Derived Fuel (RDF) is a form of solid waste utilization that is used from industries and households which have a high calorific value which can be used as a new alternative fuel. RDF is the treatment of waste which is used as an alternative energy material. The materials used to make RDF in this study are coffee grounds and bagasse. For the manufacture of coffee grounds and bagasse are mixed and adhesive is added. The mixture ratio is 100: 0, 30: 70,50: 50,70: 30, and 0: 100 for adhesive concentration using 10%, 20%, and 30%. The finished RDF-5 is tested by testing the burn time. Tests were carried out at the Laboratory of Mechanical Engineering Education, FKIP UNS. The method used an experimental method. The variables examined in this study are the independent variables, the dependent variable and the control variable. The free variation consists of variations between the composition of coffee grounds and bagasse with the following ratios 100: 0, 70:30, 50:50, 30:70, and 0: 100 as well as variations in adhesive concentrations of 10%, 20%, and 30%. The dependent variable consists of burn time. The control variables consist of the RDF-5 printer with a pressure of 6 kg / cm2 and a filter used with a size of 10 mesh. The best test results for burning time are 30 bagasse + 70 coffee grounds mixed with 30% adhesive concentration with a result of 1370 seconds.